An assessment of the impact of COVID-19 on digital payments by households - Ravindra Baviskar; Pooja Patil; Suman Deokota; Abhilasha Sharma; Ayan Mandal (MultiTech Publisher, 2023)
The COVID-19 lockdown in India marked a pivotal moment in the adoption of digital payment methods. Beyond the conventional demographic factors that have typically been scrutinized in literature concerning payment preferences, our research highlights the considerable influence of factors such as awareness of digital payment options, smartphone and debit card accessibility, as well as government social assistance initiatives during the pandemic. Interestingly, individuals who had previously abandoned digital payments due to negative experiences reverted to these modes during this period. Our study, based on a survey conducted with 200 households in Pune, investigates the effects of COVID-19 on digital payments for household expenses. The findings of our research reveal a substantial positive impact on domestic payments within households as a direct result of the pandemic. This development is particularly encouraging as India strives to materialize its vision of becoming a highly digitized economy.